The Influence of Online Media on Muslim Radicalism among Senior High School Students - Iqbal Miftakhul Mujtahid; Rian Vebrianto; Musa Thahir; Nelly Yusro (Fakultas Agama Islam Universitas Muhammadiyah Yogyakarta, 2021)
The analysis of radicalism attitudes among students is triggered by the lack of supervision of information and communication technology usage. This study aims to find the attitude of radicalism among senior high school students based on gender. The research is designed with a quantitative approach. The data were collected using a questionnaire. This study involved 229 students selected by random sampling, with a total of 107 male and 122 female students. The data were collected using a questionnaire and essay. The data were further analysed qualitatively and quantitatively. The results of this study showed that in Part A, 34% male and 19% female students often sent and shared religious content and conflicts on social media. In Part B, 13% male and 14% female students agreed on courtship, marriages with different religion, polygamy, and divorce. In Part C, 2% male and female students are anti-ideological and uphold Islamic law. Furthermore, in Part D, 67% male and 46% female students declare non-Muslims as infidel, and war is a part of jihad.